2018
DOI: 10.7150/ijbs.23489
|View full text |Cite
|
Sign up to set email alerts
|

Instillation of particulate matter 2.5 induced acute lung injury and attenuated the injury recovery in ACE2 knockout mice

Abstract: Inhaled particulate matter 2.5 (PM2.5) can cause lung injury by inducing serious inflammation in lung tissue. Renin-angiotensin system (RAS) is involved in the pathogenesis of inflammatory lung diseases and regulates inflammatory response. Angiotensin-converting enzyme II (ACE2), which is produced through the angiotensin-converting enzyme (ACE)/angiotensin II (Ang II) axis, protects against lung disease. However, few studies have focused on the relationships between PM2.5 and ACE2. Therefore, we aimed to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 57 publications
6
119
0
4
Order By: Relevance
“…Although the effect of PM 10 on ACE2 expression in human airway cells has not previously been reported, our findings are compatible with an animal study that reported lung ACE2 protein expression in wild type mice increased by 1.3 fold at 2 days post intratracheal instillation of urban PM 2.5 (11). A putative protective effect of increased pulmonary ACE2 was suggested in this mouse model by complete recovery of PM-induced acute lung injury in wild type mice, and incomplete recovery in ACE2 knockout mice (11). We therefore speculate that increased ACE2 expression may, on one hand, be a beneficial response to PM exposure, but on the other hand presents a Trojan horse to the SARS-CoV-2 virus.…”
Section: Discussionsupporting
confidence: 92%
“…Although the effect of PM 10 on ACE2 expression in human airway cells has not previously been reported, our findings are compatible with an animal study that reported lung ACE2 protein expression in wild type mice increased by 1.3 fold at 2 days post intratracheal instillation of urban PM 2.5 (11). A putative protective effect of increased pulmonary ACE2 was suggested in this mouse model by complete recovery of PM-induced acute lung injury in wild type mice, and incomplete recovery in ACE2 knockout mice (11). We therefore speculate that increased ACE2 expression may, on one hand, be a beneficial response to PM exposure, but on the other hand presents a Trojan horse to the SARS-CoV-2 virus.…”
Section: Discussionsupporting
confidence: 92%
“…These authors have reported it as a "double hit hypothesis" because both NO 2 and PM 2.5 are described as responsible for increasing the severity in respiratory and associated other diseases and COVID-19 in Italy. Similar study done in mice model indicates that PM 2.5 chronic exposure is highly responsible for upregulate angiotensin converting enzyme expression (Aztatzi-Aguilar et al 2015;Lin et al 2018). Therefore, the authors had concluded that patients who breathe polluted air that exceeds the normal limit of PM 2.5 are at the higher risk of experiencing the severity of COVID-19 once they get infected.…”
Section: Relation Among Pm 25 Mediated Ace-2 Expression and Covid-19mentioning
confidence: 82%
“…Acute PM 2.5 exposure enhances pulmonary oxidative stress and inflammatory responses and deteriorates pulmonary impedance in mice [ 106 ]. C57BL/6 mice that were exposed to PM 2.5 demonstrated a significant inflammatory response via the elevation of MCP-1 and neutrophils in the lung tissue [ 107 ]. ACE2 knockdown will enhance inflammatory response, tissue remodeling and attenuate injury repair in PM 2.5 -induced acute lung injury via p-STAT3 and p-ERK1/2 signaling pathways [ 108 ].…”
Section: In Vivo Studies Of Pm 25 -Induced Dammentioning
confidence: 99%